Contemporary Developments in Behavioural Finance - Virigineni, Mydhili; Rao, M. Bhaskara (International Journal of Economics and Financial Issues, 2017)
Investors need not be rational for markets to be efficient. The axiom of efficient market hypothesis that it is not possible to earn excess profits because the available information gets factored in instantaneously fell flat due to influence of human behaviour on the investment process. Exuberance of investors escalates asset values unduly on the back of financial irrationality. The intersection of human behaviour and the investment decisions has since evolved as ‘behavioural finance. Research demonstrates that investment decision-making process is more human than analytical, owing to behavioural biases. Recent studies in prospect theory and heuristic decision-making process focused more on investor behaviour causing market anomalies. At a time when irrational behaviour is demonstrated not only in security markets but also in other markets such as property, bullion and commodities, this paper explores the contemporary research in behavioural finance. Keywords: Behavioural finance, Capital market, Financial irrationality, Irrational behaviour. JEL Classifications: M10, M20, M50